The importance of institucional linkages for the development of multiple borer resistant maize hybrids - Overman, J.L.
Sumario (En)
Ilus.; 5 ref.
Keywords: ZEA MAYS; HIBRIDOS; LEPIDOPTERA; RESISTENCIA A LAS PLAGAS; INSTITUCIONES DE INVESTIGACION